2020
DOI: 10.1371/journal.pone.0232902
|View full text |Cite
|
Sign up to set email alerts
|

Advance hybrid medical watermarking algorithm using speeded up robust features and discrete cosine transform

Abstract: In the continuous development of computer network technology, multimedia technology and information technology, digitization has become the main means of displaying information, thus facilitating the storage, copying and dissemination of digital multimedia information. In this context, there are no restrictions on arbitrary editing, copying, modification, and dissemination of digital images, music, etc., which leads to various social problems such as information security, copyright disputes, and piracy. With t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Against geometric and traditional attacks, experiments demonstrated good invisibility and robustness of the method. Additionally, the tests revealed that it is able to protect images successfully with a normalized correlation coefficient value of more than 90% [8]. The Least Significant Bit (LSB) approach was modified using three output metrics: PSNR, MSE, and SSIM.…”
Section: Literature Surveymentioning
confidence: 99%
“…Against geometric and traditional attacks, experiments demonstrated good invisibility and robustness of the method. Additionally, the tests revealed that it is able to protect images successfully with a normalized correlation coefficient value of more than 90% [8]. The Least Significant Bit (LSB) approach was modified using three output metrics: PSNR, MSE, and SSIM.…”
Section: Literature Surveymentioning
confidence: 99%
“…Recently, a SURF-DCT based image watermarking has been proposed [ 46 ]. First, the watermark is encrypted using chaotic encryption technology in order to enhance its security.…”
Section: Previous Workmentioning
confidence: 99%
“…In quaternion matrix f (m, n), m, n denotes the position of the row and the column of the matrix, and its Fourier transform frequency-domain coordinates are expressed by (u, v) [28]. As quaternion does not satisfy the law of multiplication and exchange, there are three forms of AFT: left transform, right transform, and double-sided transform, which can be expressed as shown below.…”
Section: Quaternion Fourier Transformmentioning
confidence: 99%
“…In the research of digital image watermarking technology, many algorithms currently utilize grayscale images as carrier images. Even if the carrier images are color images, most of them utilize grayscale [35] or three-channel separate processing methods [27]. Since the color components of the color image have a very strong spectral correlation, however, such schemes do not consider the integrity of the color image and the correlation between the color components, and therefore the color image cannot be processed well.…”
Section: Introductionmentioning
confidence: 99%